l-Arabinose triggers its own uptake via induction of the arabinose-specific Gal2p transporter in an industrial Saccharomyces cerevisiae strain - Oehling, Verena; Klaassen, Paul; Frick, Oliver; Dusny, Christian; Schmid, Andreas (Biotechnology for biofuels, 2018)
Bioethanol production processes with using lignocellulosic biomass as feedstock are challenged by the simultaneous utilization of pentose and hexose sugars from biomass hydrolysates. The pentose uptake into the cell represents a crucial role for the efficiency of the process. The focus of the here presented study was to understand the uptake and conversion of the pentose l-arabinose in and reveal its regulation by d-glucose and d-galactose. Gal2p-the most prominent transporter enabling l-arabinose uptake in wild-type strains-has an affinity for the transport of l-arabinose, d-glucose, and d-galactose. d-Galactose was reported for being mandatory for inducing expression. expression is also known to be regulated by d-glucose-mediated carbon catabolite repression, as well as catabolite inactivation. The results of the present study demonstrate that l-arabinose can be used as sole carbon and energy source by the recombinant industrial strain DS61180. RT-qPCR and RNA-Seq experiments confirmed that l-arabinose can trigger its own uptake via the induction of expression. Expression levels of during growth on l-arabinose reached up to 21% of those obtained with d-galactose as sole carbon and energy source. l-Arabinose-induced expression was also subject to catabolite repression by d-glucose. Kinetic investigations of substrate uptake, biomass, and product formation during growth on a mixture of d-glucose/l-arabinose revealed impairment of growth and ethanol production from l-arabinose upon d-glucose depletion. The presence of d-glucose is thus preventing the fermentation of l-arabinose in DS61180. Comparative transcriptome studies including the wild-type and a precursor strain delivered hints for an increased demand in ATP production and cofactor regeneration during growth of DS61180 on l-arabinose. Our results thus emphasize that cofactor and energy metabolism demand attention if the combined conversion of hexose and pentose sugars is intended, for example in biorefineries using lignocellulosics.